Reforma curricular, avaliação em larga escala e PISA: um olhar a partir de percepções docentes - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
This research aims to analyze the perceptions that mathematics teachers in service have about mathematical literacy, proposed by PISA and BNCC. In this way, we sought to answer the following question: What are the perceptions that Basic Education Mathematics teachers have about BNCC, about PISA, and about what Mathematical literacy is? The investigation started with the premise that there is a gap in the initial and continuing training of teachers, regarding the concept of mathematical literacy. The theoretical framework seeks to be anchored in curriculum reforms, large-scale assessments, and mathematical literacy, focusing on PISA and BNCC. In addition, it presents how the policies of international assessment influenced curricular reforms in Brazilian education, then highlighted the influence of PISA on the BNCC. The research has a predominantly qualitative approach, but techniques of the quantitative approach were also used. Data were collected, in the year 2019, through questionnaires, and the subjects participating in the research were 106 mathematics teachers who work in the Paraná State Public Network. For the treatment of the data, Discursive Textual Analysis and Cluster Analysis were used, in which it became possible to identify four clusters, that is, four groups of teachers according to their similarities and dissimilarities, in relation to their perceptions about wide evaluation scale, PISA, BNCC and mathematical literacy. The results showed that teachers have insipient knowledge about large-scale assessment, PISA and BNCC, as well as not identifying mathematical literacy as a skill to be developed in the student, so that he can apply Mathematics and solve his problems. problems in different contexts, as pointed out in PISA and BNCC. They confuse mathematical literacy with simple mathematical literacy, that is, they consider that literating students mathematically is just teaching basic mathematics. The perceptions of Mathematics teachers led to confirm the initial hypothesis, that in his initial and continuing education, the teacher did not have sound guidelines on evaluation policies and curriculum policies, such as the BNCC, which is a current curriculum reform, as well as on literacy mathematical. In view of this, it is evident the need to address mathematical literacy, as well as educational policies for assessment and curriculum, in initial and continuing education.
Keywords: Avaliação em larga escala; BNCC; Letramento Matemático; PISA; Reforma curricular; Large-scale Assessment; BNCC; Mathematical Literacy; PISA; Educational Reform; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA